Ammonia Volatilization Losses from Paddy Fields under Controlled Irrigation with Different Drainage Treatments - Yupu He; Shihong Yang; Junzeng Xu; Yijiang Wang; Shizhang Peng (The Scientific World Journal)
The effect of controlled drainage (CD) on ammonia volatilization (AV) losses from paddy fields under controlled irrigation (CI) was investigated by managing water table control levels using a lysimeter. Three drainage treatments were implemented, namely, controlled water table depth 1 (CWT1), controlled water table depth 2 (CWT2), and controlled water table depth 3 (CWT3). As the water table control levels increased, irrigation water volumes in the CI paddy fields decreased. AV losses from paddy fields reduced due to the increases in water table control levels. Seasonal AV losses from CWT1, CWT2, and CWT3 were 59.8, 56.7, and 53.0 kg N ha−1, respectively. AV losses from CWT3 were 13.1% and 8.4% lower than those from CWT1 and CWT2, respectively. A significant difference in the seasonal AV losses was confirmed between CWT1 and CWT3. Less weekly AV losses followed by TF and PF were also observed as the water table control levels increased. The application of CD by increasing water table control levels to a suitable level could effectively reduce irrigation water volumes and AV losses from CI paddy fields. The combination of CI and CD may be a feasible water management method of reducing AV losses from paddy fields.